Influence of light additional arm cranking exercise on the kinetics of VO2 in severe cycling exercise - Billat, V. L.; Hamard, L.; Bocquet, V.; Demarie, S.; Beroni, M.; Petit, B.; Koralsztein, J. P. (International Journal of Sports Medicine, 2000)
This study examined the influence of light additional arm cranking exercise on the VO2 slow component observed during severe cycling exercise. During incremental tests, eleven triathletes exercised to exhaustion cycling with leg, cranking with arm and combined arm and leg cranking and cycling (arm work-rates being set at the third of leg work rates) to determine arm, leg and combined arm and leg lactate threshold and VO2max. After these incremental tests subjects performed in random order severe exercises until exhaustion at work-rates corresponding to the lactate threshold + 50% of the difference to the work rate associated with VO2max and the lactate threshold, i.e., delta50: 1) with legs only (leg delta50) 2) leg delta50 plus a very light arm cranking exercise at 25 % of the arm lactate threshold (Ldelta50 + A25). VO2 slow component was the increase of VO2 (in ml x min(-1)) between the third and the sixth minute of exercise (deltaVO2 63 min). Results showed 1) Nine of the eleven triathletes had a VO2 slow component in arm delta50; 2) a light cycle arm exercise (25% of lactate threshold) added to a severe leg cycle exercise did not decrease time to exhaustion in severe exercise (493 +/- 154s vs 418 +/- 84, P=0.4); 3) For the five subjects who had a VO2 slow component in leg cycling, the addition of a light arm exercise (25% of arm LT) decreased the VO2 slow component significantly (from 457 +/- 173 ml x min(-1) for leg delta50 to 111 +/- 150 ml x min(-1) for Ldelta50 + A25, Z = -2.0, P = 0.04). In conclusion, light additional arm cranking decreases the VO2 slow component in severe cycling. Further studies are needed to confirm the hypothesis that extra work due to an increasing handgrip on the handlebars may contribute to the VO2 slow component in cycling.